Video camera monitoring to detect changes in haemodynamics - Daly, J (2016)
Patients in hospital can be prone to sudden, life-threatening changes in their cardiovascular state. Haemodynamic parameters such as blood pressure, pulse transit time (PTT) and perfusion can be monitored in clinical situations to identify these changes as early as possible. Continuous blood pressure is usually monitored using a catheter placed into a major artery, but this is invasive and involves risk to the patient. In the last decade, the field of non-contact vital sign monitoring has emerged, with growing evidence that the remote photoplethysmogram (rPPG) signal can be used to estimate vital signs using video cameras. If the analysis of the rPPG signal can be expanded to include the estimation of haemodynamic parameters, it could result in methods for the continuous, non-contact monitoring of a subject's haemodynamic state. In a physiology study, a series of video recordings were made of 43 healthy volunteers. The subjects sat in a purpose-built chamber, and the composition of the air was carefully adjusted to cause the subjects to experience large, controlled changes in blood oxygen levels. To validate the video camera algorithms, reference data were also collected. Along with the volunteer study, a clinical study was performed to acquire data in a challenging clinical environment. Data were collected from patients on haemodialysis in the Renal Unit, a population likely to experience sudden changes in haemodynamics. The reference data from the Renal Unit study were analysed to determine the extent to which PTT and mean arterial pressure (MAP) are related. The correlation coefficients and linear fits were found on a global and a per-subject basis. In addition, the video recordings from the Physiology study were processed to derive rPPG signals, and these signals were analysed to obtain estimates for PTT. Local rPPG signals were also derived for different regions of interest, and the waveforms were analysed using a novel application of the technique of signal averaging to produce spatial maps of perfusion and blood flow. The correlation between conventionally measured PTT and MAP was found to be weaker in the haemodialysis population than has been shown elsewhere in the literature, except for a sub-set of patients. The results of the video analysis showed that PTT could be estimated robustly and consistently, although direct validation of these estimates was not possible because of the different method used to calculate the reference PTT. For most subjects, the spatial mapping methods produced robust maps that were consistent over time. These results suggest that it is possible to detect changes in haemodynamics using a video camera, and that this could have applications in healthcare, providing that challenges such as subject movement and clinical validation can be overcome.